Nuprl Lemma : geo-add-length_functionality_wrt_cong
∀e:BasicGeometry. ∀x,y,x',y':Length.  ((x = x' ∈ Length) 
⇒ (y = y' ∈ Length) 
⇒ (x + y = x' + y' ∈ Length))
Proof
Definitions occuring in Statement : 
geo-add-length: p + q
, 
geo-length-type: Length
, 
basic-geometry: BasicGeometry
, 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
equal: s = t ∈ T
Definitions unfolded in proof : 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
member: t ∈ T
, 
squash: ↓T
, 
uall: ∀[x:A]. B[x]
, 
true: True
Lemmas referenced : 
geo-add-length_wf
Rules used in proof : 
sqequalSubstitution, 
sqequalTransitivity, 
computationStep, 
sqequalReflexivity, 
lambdaFormation_alt, 
cut, 
applyEquality, 
thin, 
lambdaEquality_alt, 
sqequalHypSubstitution, 
imageElimination, 
introduction, 
extract_by_obid, 
isectElimination, 
because_Cache, 
hypothesis, 
equalitySymmetry, 
natural_numberEquality, 
sqequalRule, 
imageMemberEquality, 
hypothesisEquality, 
baseClosed, 
equalityIstype, 
inhabitedIsType
Latex:
\mforall{}e:BasicGeometry.  \mforall{}x,y,x',y':Length.    ((x  =  x')  {}\mRightarrow{}  (y  =  y')  {}\mRightarrow{}  (x  +  y  =  x'  +  y'))
Date html generated:
2019_10_16-PM-01_18_53
Last ObjectModification:
2019_03_04-PM-04_54_53
Theory : euclidean!plane!geometry
Home
Index